The potential of Ti3C2Tx-KH2PO4 and Ti3C2Tx-chitosan in the efficient removal of cesium from nuclear wastewater - Shanli Nezami; Ahad Ghaemi; Taher Yousefi (Scientific Reports)
Abstract Ti3C2Tx is synthesized from Ti3AlC2 by two common methods, HF and HF in situ. The synthesis approach is very practical regarding the structure, morphology, space between layers, type and number of surface-active sites and its specific surface. XRD, SEM, EDS, FTIR and BET analyzes were used to investigate the structure, morphology, type and number of surface-active sites. Under the operating conditions of cesium initial concentration ~ 150 ppm, ambient temperature, pH ~ 7.00 and time of 60 min, the cesium adsorption intensity with Ti3C2Tx-HF and Ti3C2Tx-HF in situ was obtained as 194 and 219.5 mg.g− 1, respectively. The structural results of modification with KH2PO4 show that in this modification, in addition to the increase of hydroxyl functional groups, the distance between the layers has also increased and the cesium adsorption intensity has increased to 338.75 mg.g− 1 under the above operating conditions. Meanwhile, in modification with Chitosan by increasing the frequency of functional groups and specific surface up to 3 times the effective specific surface of Ti3C2Tx-HF in situ, no significant change in the cesium adsorption intensity has been observed (247.5 mg.g− 1). Experiments were conducted to evaluate the effect of parameters of initial concentration of Cs+ (250 − 50 ppm), time (30–60 min), ambient temperature (298.15–318.15 K), solution pH (3.0–11.0) with the help of RSM design. RSM results show that the pH parameter is one of the most important parameters affecting the cesium adsorption intensity with Ti3C2(OH)x and Ti3C2(OH)x-KH2PO4. Also, with the increase in temperature, the adsorption intensity should increase. It is shown in the isotherm modeling that R2 matches well with the Freundlich isotherm model, which is based on the layered structure of Ti3C2(OH)x and Ti3C2(OH)x-KH2PO4 and the presence of active sites with different energy levels, which leads to heterogeneous adsorption. The consistency will be of the adsorbent selectivity investigation shows that the Cs+ hydration radius plays a decisive role in its high adsorption potential. Reduction of MXene by 0.1 M HCl was carried out in 3 steps. The experimental results show that 15% absorption has been achieved in the third stage. The results of structural analysis show that its structure has not changed and the reduction of active sites as a result of washing with acid has led to a decrease in adsorption.